Short-selling prior to analyst recommendations - QU, Can (Institutional Knowledge at Singapore Management University, 2010)
This paper investigates short-selling five days prior to analyst recommendations by using a complete data set from Reg SHO database during January, 2005 to July, 2007. Empirical tests uncover the evidence that short-sellers significantly increase their short positions prior to negative analyst recommendations, which is consistent with the informed trading hypothesis. This finding is robust to model specification. Further, this paper also examines which of the two competing hypotheses-prediction and tipping-could better explain short-sellers’ informative front-running. The tests indicate that short-sellers use book-to-market ratio as a filter to narrow down their pool of candidates, while market capitalization doesn’t play a role in short-sellers’ decision process. However, earnings management seems to influence short-sellers’ attitude towards analyst recommendations. For these “aggressive” firms, short-selling transactions seem to deviate from analyst recommendations, which imply that short-sellers may scrutinize the firms by themselves rather than mechanically listen to analysts’ tips. This piece of evidence tends to favor prediction hypothesis.